Hubungan Diabetes Distress dengan Perilaku Perawatan Diri pada Penyandang Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Rambipuji Kabupaten Jember (Correlation between Diabetes Distress and Selfcare Behaviour in People with Type 2 Diabetes Mellitus i - Ary Januar Pranata Putra; Nur Widayati; Jon Hafan Sutawardana (Pustaka Kesehatan, 2017)
Diabetes distress is an emotional problem that is directly related to the burden and worriesresulted from living with chronic disease. Stress has an impact on self-care behaviour whichaffects metabolic control. This study aimed to analyze the correlation between diabetesdistress and self-care behaviour in people with type 2 diabetes mellitus.This research appliedan observational analytic design with cross sectional approach. A total of 66 respondents wereenrolled in this study by using quota sampling technique. Data collection was conducted byadministering questionnaires of Diabetes Distress Scale (DDS) and Summary of Diabetes SelfCare Activities (SDSCA). Data were analyzed by using Spearman test with significance level of0.05. The result showed that the mean value of diabetes distress and self-care behaviour was2.16 and 3.97 respectively. The p value was 0.000 (p <0.05) with the correlation (r) of -0.629.There was significant correlation between diabetes distress and self-care behaviour. Thecorrelation was strong and negative which means the higher the level of diabetes distress thelower the performance of self-care behaviour. This study suggests the importance of assessingexperienced distress to optimize self-care behaviour in type 2 diabetes patients.Keywords: type 2 diabetes mellitus, diabetes distress, self-care behaviour